Gazing Homeland Politics: A Case Study of The Political Engagement of The Indonesian Diaspora Group Manila - Triwardani, Reny (Commsphere: Jurnal Ilmu Komunikasi, 2023)
As per the data provided by KPU, the 2019 Election witnessed the participation of 2,058,191 voters amongst the Indonesian Diaspora. This number marks an increase of 19,480 voters from the previous Presidential Election held in 2014, wherein 2,038,711 registered voters across 130 Indonesian representatives abroad had cast their votes. The surge in Indonesian Diaspora voters indicates their significant role in election contests. The involvement of the Indonesian Diaspora in homeland politics is significantly impacted by their ability to stay informed about current events and maintain solid familial ties with their home country. Online platforms and social media play an essential role in keeping the Diaspora apprised of political developments and expanding their understanding of the issues. This article explores the political engagement of Indonesian diaspora communities residing in Metro Manila, Philippines, in the lead-up to the 2019 elections. The research centers on a church member group in ICF Makati, which is conventionally regarded as a non-political organization. The study employs a blend of observations and interviews to investigate how the Indonesian diaspora community participates in political affairs. Specifically, the research scrutinizes how they deliberate on topics concerning their homeland's politics and exchange their perspectives on current political events. Findings indicate that the Indonesian Diaspora is becoming more discerning of the political landscape in their homeland. This is primarily due to the widespread political discourse taking place online. Social media platforms have made it effortless for people to remain actively informed about political developments in their home country. Additionally, the Indonesian Diaspora has demonstrated a heightened interest in homeland politics, particularly in the lead-up to elections, to express their imagined nationalism. Keywords: Diaspora group, Presidential Election 2019, Political Engagement, Social Media usage